Integration of New Features for Telerobotic Surgery into The Mirosurge System - Rainer Konietschke; Davide Zerbato; Rogério Richa; Andreas Tobergte; Philippe Poignet; Florian A. Fröhlich; Debora Botturi; Paolo Fiorini; Gerd Hirzinger (Applied Bionics and Biomechanics)
Minimally invasive robotic surgery has gained wide acceptance recently. Computer-aided features to assist the surgeon during these interventions may help to develop safer, faster, and more accurate procedures. Especially physiological motion compensation of the beating heart and online soft tissue modelling are promising features that were developed recently. This paper presents the integration of these new features into the minimally invasive robotic surgery platform MiroSurge. A central aim of this research platform is to enable evaluation and comparison of new functionalities for minimally invasive robotic surgery. The system structure of MiroSurge is presented as well as the interfaces for the new functionalities. Some details about the modules for motion tracking and for soft tissue simulation are given. Results are shown with an experimental setup that includes a heart motion simulator and dedicated silicone organ models. Both features are integrated seamlessly and work reliably in the chosen setup. The MiroSurge platform thus shows the potential to provide valuable results in evaluating new functionalities for minimally invasive robotic surgery.